Measurement of the Upsilon(1S), Upsilon(2S), and Upsilon(3S) cross sections in pp collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; et al. (2013)
The Υ(1S), Υ(2S), and Υ(3S) production cross sections are measured using a data sample corresponding to an integrated luminosity of 35.8±1.4pb-1 of proton-proton collisions at s=7TeV, collected with the CMS detector at the LHC. The Υ resonances are identified through their decays to dimuons. Integrated over the Υ transverse momentum range pTΥ<50GeV/c and rapidity range |yΥ|<2.4, and assuming unpolarized Υ production, the products of the Υ production cross sections and dimuon branching fractions areσ(pp→Υ(1S)X)B(Υ(1S)→μ+μ-)=(8.55 0.05-0.50+0.56±0.34)nb,σ(pp→Υ(2S)X)B(Υ(2S) →μ+μ-)=(2.21±0.03-0.14+0.16±0.09)nb,σ(pp→Υ(3S)X)B(Υ(3S)→μ+μ-)=(1.11±0.02-0.08+0. 10±0.04)nb, where the first uncertainty is statistical, the second is systematic, and the third is from the uncertainty in the integrated luminosity. The differential cross sections in bins of transverse momentum and rapidity, and the cross section ratios are presented. Cross section measurements performed within a restricted muon kinematic range and not corrected for acceptance are also provided. These latter measurements are independent of Υ polarization assumptions. The results are compared to theoretical predictions and previous measurements. © 2013 CERN.